PELESTARIAN BUDAYA LOKAL KAMPUNG NAGA SESEBAGAI PEREKAT SOLIDARITAS SOSIAL MASYARAKAT - Encup Supriatna (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
This study aims to determine the preservation of local culture of simple living heritage as the glue of social solidarity of the people of Kampung Naga. This study uses qualitative methods with data collection techniques in the form of observation, interviews, documentation and literature study. Analysis of the data using the interactive model of Miles & Huberman. The sustainability of the simple living heritage of the Kampung Naga community is seen in terms of the lifestyle, the tools used, the buildings that are still the same until now and by doing so using the characteristics of simplicity and traditional, community involvement whose overall role is still active supported by a high level of awareness and strong sense of shared responsibility. So that it can be an external stimulus as an adhesive for community social solidarity that is applied in daily life by the form of cooperation in mutual cooperation, mutual help among neighbors or community groups.